A comparison of results following the treatment of placenta accreta and placenta increta using high-intensity focused ultrasound followed by hysteroscopic resection. (1st January 2021) - Lin, Zhenjiang; Gong, Chunmei; Huang, Qin; Zhang, Zhendong; Wang, Donghong; Yuan, Li; Wang, Xi; An, Qiang; Chen, Dayong; Liu, Song; Zou, Xiaofeng; Setzen, Raymond; et al.
Abstract: Objective: To compare the safety and efficacy of high-intensity focused ultrasound (HIFU) followed by hysteroscopic resection for different placenta accreta spectrum disorders. Materials and methods: Thirty-four patients with placenta accreta, placenta increta, or placenta percreta were treated with USgHIFU from January 2016 to December 2019 and were retrospectively reviewed. The patients were classified into three categories according to the relationship between the trophoblastic villi and the myometrium, based on magnetic resonance imaging (MRI). Fifteen patients were classified as placenta accreta, 17 patients were classified as placenta increta, and 2 were classified as placenta percreta. All patients completed follow-up. Treatment efficacy and safety were evaluated. Results: No significant differences in baseline characteristics and results of HIFU ablation were observed between the patients with placenta accreta and those with placenta increta. The return of HCG levels to normal was longer in patients with placenta accreta compared with patients with placenta increta, while no significant difference was observed in the amount of intraoperative blood loss, the return of normal menstruation and the length of hospital stay. Conclusions: HIFU treatment followed by hysteroscopic resection is safe and effective in the treatment of patients with placenta accreta and placenta increta.